1998
DOI: 10.1177/0032885598078004004
|View full text |Cite
|
Sign up to set email alerts
|

California's Inmate Classification System: Predicting Inmate Misconduct

Abstract: The goal of this article is to provide insight on the predictive value of California's inmate classification system. The authors argue that the current system is based heavily on an inmate's sentence length and that such an indicator provides little or no predictive value for inmate misconduct and is therefore not meeting the policy objectives assigned to classification and risk assessment. The authors use a large data set (N = 13,000) based on incident reports from 1992 to 1994 to test the hypothesis that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 3 publications
1
32
0
Order By: Relevance
“…Age at incarceration has generally been found to be the most robust individual-level predictor of misconduct; younger inmates are more likely to engage in disruptive behavior (Fernandez & Neiman, 1998;Flanagan, 1983;Gaes & McGuire, 1985;Gaes, Wallace, Gilman, Klein-Saffran, & Suppa, 2002;Goetting & Howsen, 1986;Jensen, 1977;Jensen & Jones, 1976;Jiang & Winfree, 2006;McCorkle, 1995;Myers & Levy, 1978;Steiner & Wooldredge, 2009;Toch & Adams, 1986;Toch et al, 1989;Welsh et al, 2007;Wooldredge, Griffin, & Pratt, 2001;Zamble & Porporino, 1988).…”
Section: Factors Associated With Prison Misconductmentioning
confidence: 99%
See 3 more Smart Citations
“…Age at incarceration has generally been found to be the most robust individual-level predictor of misconduct; younger inmates are more likely to engage in disruptive behavior (Fernandez & Neiman, 1998;Flanagan, 1983;Gaes & McGuire, 1985;Gaes, Wallace, Gilman, Klein-Saffran, & Suppa, 2002;Goetting & Howsen, 1986;Jensen, 1977;Jensen & Jones, 1976;Jiang & Winfree, 2006;McCorkle, 1995;Myers & Levy, 1978;Steiner & Wooldredge, 2009;Toch & Adams, 1986;Toch et al, 1989;Welsh et al, 2007;Wooldredge, Griffin, & Pratt, 2001;Zamble & Porporino, 1988).…”
Section: Factors Associated With Prison Misconductmentioning
confidence: 99%
“…Some studies found African-Americans to be disproportionately involved in prison misconduct (Fernandez & Neiman, 1998;Goetting & Howsen, 1983, 1986Toch et al, 1989). Gover, Perez, and Jennings (2008) suggested that the effect may be gender specific: nonwhite females, on average, had a higher number of infractions than white females, but the effect of race was nonsignificant among male inmates.…”
Section: Factors Associated With Prison Misconductmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, records of prison misconduct tend to be more extensive for ill-educated relatively young prisoners who began their criminal careers relatively early (Chapman, 1981;Chowanec, Josephson, Coleman, & Davis, 1991;Fernandez & Neiman, 1998) and this is also true of SIB prisoners (Lanes, in press b). Noted, though, is that being housed at a maximum security facility may result in an individual incurring a greater number of prison misconducts (Fernandez & Neiman, 1998;Scott & Gerald, 2005) due to facility security level, size, and population characteristics (e.g., more violent offenders than non-violent ones) (Frazee, 2003).…”
Section: Administrative Segregation and Who Gets Placed Therementioning
confidence: 99%